Characterized Gene Repertoires and Functional Gene Reference for Forensic Entomology: Genomic and Developmental Transcriptomic Analysis of Aldrichina grahami (Diptera: Calliphoridae). Issue 3 (9th February 2022) - Meng, Fanming; Han, Han; Wang, Mo; Jiang, Yangshuai; Pi, Zhiyun; Qu, Yihong; Liu, Zhuoying; Cai, Jifeng
Abstract: Many flies of Diptera are common entomological evidence employed in forensic investigation. Exploring the existence of inter- and intra-species genomic differences of forensically relevant insects is of great importance. Aldrichina grahami is a common blow fly species of forensic importance. The present study characterized the gene repertoires of A. grahami, and provides insights into issues related to forensic entomology, such as necrophagous behavior, gene family features, and developmental patterns. Gene families were clustered and classified according to their function in different aspects of the necrophagous lifestyle, generating several gene repertoires. The genes under positive selection pressure and evolutionary changes were screen and identified. Moreover, genes that exhibited potential prediction value in the post mortem interval (PMI) estimation and development of immature stages were subjected to analysis based on the developmental transcriptome. Related insect species were compared at the genomic level to reveal the genes associated with necrophagous behaviors. The expression of selected genes in separated repositories was verified using qPCR. This work was conducted using a high-quality chromosome-level genome assembly of A. grahami and its developmental transcriptome. The findings will facilitate future research on A. grahami and the other forensically important species.